Parkinson’s Disease Progression: Implicit Acquisition, Cognitive and Motor Impairments, and Medication Effects - Pavão, Rodrigo; Helene, André F.; Xavier, Gilberto F. (Frontiers in Integrative Neuroscience, 2012)
Parkinson’s disease (PD) symptoms have been collectively ascribed to malfunctioning of dopamine-related nigro-striatal and cortico-striatal loops. However, some doubts about this proposition are raised by controversies about the temporal progression of the impairments, and whether they are concomitant or not. The present study consists of a systematic revision of literature data on both functional PD impairments and dopaminergic medication effects in order to draw a coherent picture about the disease progression. It was done in terms of an explanatory model for the disruption of implicit knowledge acquisition, motor and cognitive impairments, and the effects of dopaminergic medication on these functions. Cognitive impairments arise at early stages of PD and stabilizes while disruption of acquisition of implicit knowledge and motor impairments are still in progression; additionally, dopaminergic medication reduces motor impairments and increases disruption of acquisition of implicit knowledge. Since this model revealed consistency and plausibility when confronted with data of others studies not included in model's formulation, it may turn out to be a useful tool for understanding the multifaceted characteristics of PD.